O PROGRAMA ESCOLAS INTERCULTURAIS DE FRONTEIRA (PEIF) COMO POLITICA LINGUISTICA EDUCACIONAL: ESTUDO NA FRONTEIRA DAS CIDADES DE SÃO BORJA (BR) E SANTO TOMÉ (AR) - Lorenzetti, Alejandro Néstor (2016)
This work aims to describe the current status of the Inter-cultural at the Frontier Schools Program (PEIF) in schools in the cities of Santo Tomé (Argentina) and São Borja (Brazil), and to understand the effects of the implementation of this Linguistic Policy in this region, having by general objective to understand the place of languages at the PEIF. For this, we conducted a field study in four schools, two on each side of the border, during two years in which we traveled collecting documents, photographs, recording numerous interviews and video records, and accompanying teachers in training activities and some classes. We construct a theoretical framework linked to Applied Linguistics, articulating the discussions about culture, globalization and postcoloniality with Ethnography, Linguistic Policy, and the contributions of dialogical discourse analysis (ADD) of Bakhtin's Circle. From this conjunction was born the organization "by layers" of this text, and the analysis "from top to bottom" proposed by the Circle. In the first layer (introduction) we present the research and a historical course of more than a decade of PEIF. We also review and present a brief analysis of the academic productions that focus on this Program, specifically Brazilian theses and dissertations, aiming to insert this work in an academic context whose constitution is also part of the history of the object of study. From this set we obtained some conclusions that later integrate our general analysis. In the second layer (first chapter) we make a historical presentation of the formation of the field of Linguistic Policies as a political and scientific-academic subject, guided by three authors: Ricento (2000) Spolsky (2004) and Johnson (2013). We link PL with PEIF and present issues related to bilingualism, Linguistic Ideologies (IL) and Inter-comprehension between languages. In the third layer (second chapter) we problematize frontiers in the new context. Using the theoretical framework of postcoloniality (APPADURAI, 2004; BABHA, 2006; G. CANCLINI, 1989, 1997; SILVA, 2012) we introduce the questions related to hybrid cultures and identities, to national identities, and especially to the panorama of the studied region through the concept of ideolandscape. The fourth layer (third chapter) develops the ethnographic methodology, supported by Erickson (1985) and Blommaert and Jie (2006) and we briefly present dialogic discourse analysis (ADD) (VOLOSHINOV, 2006). The fifth layer (fourth chapter) concentrates the discussion of the data constructed from the field experience, through the ADD, generating categories of analysis. It is here that, in the voices of protagonists, the different operations of the IL, the effects of the PL and the conflicts arising from the different conceptions operating in the teachers and institutions involved appear. A sixth layer contains the conclusions of the paper, which summarize a history of good political intentions, institutional conflicts, deletions, and historical and emotional ties between the protagonists, the actors who wrote an important chapter in frontier integration and education at the frontiers.